RFK - Underschultz, Derick V.; Steinberg, Hank; Roache, Linus 1964-; Paymer, David ca. 20. Jh; Donovan, Martin 1957-; Cromwell, James 1940-; Vargas, Jacob 1971-; Rhames, Ving 1959- (StudioWorks Entertainment, 2003)
The final five years of Robert F. Kennedy's life are looked at in this drama, starting with JFK's assassination in 1963, to his own tragic death in 1968
Original: USA, 2002 (TV-Spielfilm)
DVD - Originally broadcast by FX Aug. 25, 2002
Keywords: Kennedy, Robert F. / 1925-1968 / Last years / Drama; Presidents / Brothers and sisters / United States / Drama; Senators / New York (State) / Drama; USA; Film; DVD-Video